Consumptive Behavior: How Religiousity Moderation Affect in Financial Literacy and Self-Concept Student Digital Wallet Users - Nur Aeni Waly; Mitta Muthia Wangsi; Bekti Wiji Lestari; Nugroho Dwi Prihandoko; Nurhani Nurhani; Aji Masyhur Nurlily (UNIVED Press, 2026)
This study aims to present empirical evidence that can be used as information related to how the role of religiosity moderates financial literacy and self concept towards the consumptive behavior of Islamic students who use digital wallets and has social intervention from the majority of non-Muslim students. This research is using quantitative methode. The sampling used purposive sampling technique and used the Slovin's formula to get the result 97 respondents. The data collection method used is a questionnaire structured. this research uses the moderated regression analysis (MRA) technique with the SPSS27 application. This research found that financial literacy has a negative and insignificant effect on consumptive behavior, self concept has a positive and significant effect on consumer behavior, Financial literacy with religiosity has not significant effect towards consumptive behavior, and Self concept with religiosity has significant effect towards consumptive behavior. The value from this research give the insight for educational institutions and financial education institutions to emphasize the importance of developing self concept and religiousity integration in student financial management program.